Infrastructural and social aspects of ICT dissemination in rural areas in Ukraine in juxtaposition with other post-transition countries: State of play and prospects for rural development - Aleksandra Synowiec (Journal of Risk and Financial Management, 2021)
The objective of this study is to identify the current state of, and the prospects for, information and communication technologies (ICT) dissemination in rural areas in Ukraine in juxtaposition with other post-transition countries. The spread of ICT is discussed within the frame of economic, infrastructural, and social factors affecting rural areas in Ukraine since the post-communist transition period. Information and communication technologies may support the socio-economic development of peripheral areas in many ways-including rural ones. Dissemination of ICT contributes to the emergence of sources of income, equalizes education opportunities, and increases the attractiveness of rural areas. However, the rural-urban divide in the countries of Central and Eastern Europe and other former USSR countries is still remarkable and, as a type of structural inequality, should be better recognized. The source material is based on secondary data, which consists of selected literature on the subject of rural development in Central and Eastern European Countries, strategic documents, available reports and studies of international institutions, research from agencies, state documents and statistics, and research conducted by international and domestic NGOs. In reference to the paper's objective, the method of content analysis was employed. Dissemination of ICT in rural areas in Ukraine is influenced by two groups of factors. The infrastructural divide concerning Internet access between rural and urban populations in Ukraine has been diminishing, but the issue of structural exclusion due to place of residence has still not been solved. As far as the social aspects of ICT dissemination in rural areas in Ukraine are concerned, the level of digital literacy among rural dwellers is significantly lower in comparison to urban residents. Rural areas are more exposed to the consequences of various aspects of digital exclusion.
Keywords: 330; rural areas; information and communication technologies; socio-economic development; digital divide; social change